Ceramic tile green body with high dry strength, method for manufacturing the same, and marble ceramic tile

By using brick base powder instead of raw clay in the production of marble tiles, and combining it with a specific ratio of stone powder, washed clay and medium-temperature sand, a high-dry-strength tile body is prepared, solving the problems of scarcity of raw clay and high organic matter content, thus achieving efficient production and sustainable development.

CN118439859BActive Publication Date: 2026-11-06FOSHAN CITY GANI CERAMICS CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410535748.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2026-11-06
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

In current marble tile production, the scarcity of raw clay and the abundance of organic matter make it difficult to guarantee the strength of the dry brick, affecting production efficiency and product quality.

Method used

By using brick base powder to replace the original ore clay, combined with stone powder, washed clay, medium-temperature sand and waste, a ceramic tile body with high dry strength is prepared. The body includes 40-50 parts stone powder, 20-25 parts washed clay, 28.8-35 parts medium-temperature sand, 10-12 parts waste, and 1.2-2 parts brick base powder. The process involves ball milling, granulation and firing.

Benefits of technology

It achieves high-drying-strength ceramic tile blanks that meet screen printing process standards, reduces the use of non-renewable resources, improves production efficiency and product quality, and meets the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118439859B_ABST
    Figure CN118439859B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of marble tiles, and particularly relates to a high-drying-strength tile body, a preparation method thereof and a marble tile. The application discloses a high-drying-strength tile body, which comprises the following raw materials in parts by weight: stone powder 40-50 parts, water-washed kaolin 20-25 parts, medium-temperature sand 28.8-35 parts, waste 10-12 parts, and tile bottom powder 1.2-2 parts. The tile body disclosed by the application replaces the original ore kaolin by adding the tile bottom powder, so that the high-drying-strength tile body can achieve a higher drying strength of the dry body and can achieve the process standard of silk screen printing, which will reduce the use of non-renewable resources and achieve the purpose of sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of marble ceramic tiles, and in particular to a ceramic tile body with high drying strength, its preparation method, and marble ceramic tiles. Background Technology

[0002] To more realistically reproduce the surface texture of natural marble tiles, screen printing technology is used to enrich the surface effect and layering of marble tiles. In order to meet various process requirements during production and ensure that there are no cracked tiles on the production line, the dry body strength requirement is extremely high (dry body strength ≥ 1.8MPa). In order to ensure the strength of the body, the raw materials of the body are made by introducing raw ore to achieve the required dry body strength.

[0003] Because the drying strength of the ceramic tile body is required to be high, a high proportion of raw ore is used in the raw materials to ensure the drying strength of the body. However, due to the increasing scarcity of raw ore and the current high restrictions on mining (making stable supply difficult in the long run), the drying strength of marble ceramic tile bodies is difficult to guarantee. In addition, because raw ore contains a lot of organic matter, it is difficult to exhaust air during the production process, which makes marble ceramic tiles prone to black core, which is very unfavorable to increasing the production capacity of marble ceramic tiles.

[0004] Therefore, this application provides a ceramic tile body with high drying strength, a method for preparing the same, and a marble ceramic tile. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, this invention provides a high-dry-strength ceramic tile body, its preparation method, and marble ceramic tiles. By adding brick base powder to replace the original ore clay, the ceramic tile body achieves higher dry-strength and meets the process standards for screen printing. This will reduce the use of non-renewable resources and achieve the goal of sustainable development.

[0006] The technical solution adopted by this invention to solve its technical problem is:

[0007] The primary objective of this application is to provide a ceramic tile body with high drying strength, comprising, by weight, the following raw materials:

[0008] Stone powder 40-50 parts, washed clay 20-25 parts, medium-temperature sand 28.8-35 parts, waste material 10-12 parts, brick base powder 1.2-2 parts.

[0009] Furthermore, the stone powder is one or both of potassium feldspar and sodium feldspar.

[0010] Furthermore, the chemical composition of the water-washed mud is as follows:

[0011] SiO2: 50.98-65.5%, Al2O3: 34.04-39.9%, Fe2O3: 1.3-1.5%, TiO2: 0.06%, CaO: 0.25%, MgO: 0.15-0.25%, K2O: 1.38%, Na2O: 0.12%.

[0012] Furthermore, the medium-temperature sand is one or more of potassium sand, sodium sand, and red sand.

[0013] Furthermore, the waste material is one or more of polishing slag, recycled scrap, and sewage mud.

[0014] Furthermore, the magnesium oxide content in the brick base powder is 65-80% by weight.

[0015] A second objective of this application is to provide a method for preparing a ceramic tile blank, comprising the following steps:

[0016] Prepare the corresponding raw materials according to the weight composition of the ceramic tile body; after the raw materials are fully mixed, they are ball-milled; after ball milling, they are granulated; after granulation, they are aged, dried and fired to obtain the ceramic tile body.

[0017] Furthermore, the ball milling involves mixing the mixture, water, and desiccant, and then ball milling them in a small ball mill jar.

[0018] Furthermore, after granulation, the particle size distribution is as follows: 20 mesh ≤ 2.0%, 20-40 mesh 51-56%, 40-60 mesh 34-38%, 60-100 mesh ≤ 10%, and 100 mesh ≤ 3%.

[0019] A third objective of this application is to provide a marble ceramic tile with high drying strength, comprising the ceramic tile body described above.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The ceramic tile body described in this application, by adding brick base powder to replace the original ore, achieves higher dry strength and meets the process standards for screen printing. This will reduce the use of non-renewable resources and achieve the goal of sustainable development.

[0022] 2. The marble blank described in this application has a dry strength of 1.80-2.20 MPa, a shrinkage rate of 7.50-7.70%, and a water absorption rate of 0.015-0.02%. Attached Figure Description

[0023] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0024] Figure 1This is a process flow diagram of the method for preparing the ceramic tile blank described in this application. Detailed Implementation

[0025] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention.

[0026] As used herein, “and / or” includes all combinations of any one or more of the associated listed items. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used herein, the singular forms “a,” “an,” “an,” and “the” are also intended to include the plural forms unless the context clearly indicates otherwise. Further understanding is needed; when used in this specification, “comprising” designates the stated features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or combinations thereof.

[0027] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Further understanding is that terms, such as those defined in common dictionaries, are interpreted in accordance with their meaning in the context of the relevant field and are not idealized or overly formal, unless expressly defined herein.

[0028] The exemplary invention described herein may suitably omit any one or more limiting elements, which are not specifically disclosed herein. Therefore, terms such as “comprising,” “including,” “containing,” etc., should be interpreted broadly and non-limitingly. Furthermore, the terminology used herein is for descriptive purposes without limitation, and it is unintentional to use terms that do not include any equivalent characteristics, but only to describe a portion of their characteristics; however, various modifications are possible within the scope of the invention according to the claims. Therefore, while the invention has been specifically disclosed through preferred embodiments and optional features, variations of the invention embodied by the modifications disclosed herein may be noted by those skilled in the art, and such modifications and variations are considered to be within the scope of the invention.

[0029] All raw materials or reagents used in the embodiments and comparative examples of this invention were purchased from mainstream manufacturers on the market. Those without specified manufacturers or concentrations are all analytical grade raw materials or reagents that are routinely available. There are no particular restrictions as long as they achieve the expected effect. The reaction vessels and rotary evaporators used in this embodiment were all purchased from major manufacturers on the market. There are no particular limitations as long as they achieve the expected effect. Where specific techniques or conditions are not specified in this embodiment, they should be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions.

[0030] To ensure the strength of the billet, raw ore is often introduced into the billet to achieve the required dry billet strength. The chemical composition of the raw ore is as follows:

[0031] The composition of the raw ore is as follows: SiO2: 59.58%, Al2O3: 25.98%, Fe2O3: 1.55%, TiO2: 0.26%, CaO: 0.26%, MgO: 0.3%, K2O: 1.5%, Na2O: 0.22%, and loss on ignition: 10.35%. Moreover, the raw ore contains a lot of tree roots, resulting in a lot of wood residue after ball milling. This makes it difficult to ventilate during the production process, which can easily cause the marble tiles to develop a black core.

[0032] To reduce the use of raw clay, this application provides a ceramic tile body with high dry strength by replacing raw clay with brick base powder, comprising the following raw materials by weight:

[0033] Stone powder 40-50 parts, washed clay 20-25 parts, medium-temperature sand 28.8-35 parts, waste material 10-12 parts, brick base powder 1.2-2 parts.

[0034] Specifically, the stone powder is one or both of potassium feldspar and sodium feldspar. In this application, the stone powder acts as a flux. The weight range of the stone powder is 40-50 parts, specifically any value among 40, 41, 45, and 50 parts, or any value within the range of 40-50 parts.

[0035] Specifically, the chemical composition of the water-washed mud is as follows:

[0036] The composition of the washed clay is as follows: SiO2: 50.98-65.5%, Al2O3: 34.04-39.9%, Fe2O3: 1.3-1.5%, TiO2: 0.06%, CaO: 0.25%, MgO: 0.15-0.25%, K2O: 1.38%, Na2O: 0.12%. In this application, the washed clay can enhance the drying strength of the ceramic tile, ensure its hardness during operation before sintering, and improve the physical properties of the product. The weight range of the washed clay is 20-25 parts, specifically any value from 20, 21, 22, or 25 parts, or any value within the range of 20-25 parts.

[0037] Specifically, the medium-temperature sand is one or more of potassium sand, sodium sand, and red sand. In this application, the medium-temperature sand serves to regulate the firing temperature, increase the sintering strength, and reduce costs. The weight range of the medium-temperature sand is 28.8-35 parts, specifically any value among 28.8, 29, 30, and 35 parts, or any value within the range of 28.8-35 parts.

[0038] Specifically, the waste material is one or more of polishing slag, recycled scrap, and sewage mud. The purpose of using the waste material is to utilize waste and reduce costs. The weight range of the waste material is 10-12 parts, specifically any value of 10, 11, or 12 parts, or any value within the range of 10-12 parts.

[0039] More specifically, polishing slag refers to the excess material after the semi-finished product has been ground and then pressed; the chemical composition of polishing slag is as follows:

[0040] SiO2: 68.71%, Al2O3: 20.04%, Fe2O3: 0.78%, TiO2: 0.15%, CaO: 0.79%, MgO: 1.1%, K2O: 3.65%, Na2O: 2.91%, Loss on ignition: 1.87%.

[0041] Recycled scrap refers to the collection of powder leakage from the raw material workshop and pressing workshop, as well as scrap after glazing on the glazing line; the chemical composition of recycled scrap is as follows:

[0042] SiO2: 69.62%, Al2O3: 20.12%, Fe2O3: 0.74%, TiO2: 0.13%, CaO: 0.63%, MgO: 0.89%, K2O: 3.6%, Na2O: 2.69%, Loss on ignition: 1.58%.

[0043] Wastewater cement refers to slurry leakage during the raw material workshop's slurry processing and the powder that flows into the wastewater treatment pond after washing and pressing. The chemical composition of wastewater cement is as follows:

[0044] SiO2: 65.91%, Al2O3: 20.27%, Fe2O3: 0.84%, TiO2: 0.23%, CaO: 0.86%, MgO: 0.97%, K2O: 3.51%, Na2O: 2.46%, Loss on ignition: 4.95%.

[0045] Specifically, the magnesium oxide content in the brick base powder is 65-80% by weight. In this application, the role of the brick base powder in the green body is to increase the drying strength of the green body and to act as a flux. The weight range of the brick base powder is 1.2-2 parts, specifically any value among 1.2 parts, 1.3 parts, 1.5 parts, and 2 parts, or any value within the range of 1.2-2 parts.

[0046] The chemical composition of brick base powder is as follows:

[0047] SiO2: 8.62-15%, Al2O3: 1.64-3%, Fe2O3: 0.99-2%, TiO2: 0.22-0.5%, CaO: 3.14-8%, MgO: 65-80%, K2O: 0.55-1%, Na2O: 0.02-0.05%.

[0048] A second objective of this application is to provide a method for preparing a ceramic tile blank, comprising the following steps:

[0049] Prepare the corresponding raw materials according to the weight composition of the ceramic tile body; after the raw materials are fully mixed, they are ball-milled; after ball milling, they are granulated; after granulation, they are aged, dried and fired to obtain the ceramic tile body.

[0050] Furthermore, the ball milling involves mixing the mixture, water, and desiccant, and then ball milling them in a small ball mill jar. The dispersant's function is to reduce viscosity and address the poor flowability of the slurry.

[0051] Furthermore, after granulation, the particle size distribution is as follows: 20 mesh ≤ 2.0%, 20-40 mesh 51-56%, 40-60 mesh 34-38%, 60-100 mesh ≤ 10%, and 100 mesh ≤ 3%. Particle size distribution refers to the quantity and size distribution of various particles in the powder. If the particles are too large, the dry blank strength will be lower and the shrinkage will be smaller. If the particles are too small, the dry blank strength will be higher, but it will be easy to separate into layers and the shrinkage will be larger. Both excessively large and small particles will affect the degree of sintering. The particle size distribution described in this application can ensure that the blank has good dry blank strength.

[0052] A third objective of this application is to provide a marble ceramic tile with high drying strength, comprising the ceramic tile body described above.

[0053] Example 1

[0054] A high-dry-strength ceramic tile body, comprising, by weight, the following raw materials:

[0055] 40 parts potassium feldspar, 20 parts water-washed clay, 28.8 parts potassium sand, 10 parts polishing residue, and 1.2 parts brick base powder.

[0056] The chemical composition of the washed mud is as follows:

[0057] SiO2: 56.5%, Al2O3: 39.9%, Fe2O3: 1.5%, TiO2: 0.06%, CaO: 0.25%, MgO: 0.25%, K2O: 1.38%, Na2O: 0.12%.

[0058] The chemical composition of brick base powder is as follows:

[0059] SiO2: 8.62%, Al2O3: 1.64%, Fe2O3: 0.99%, TiO2: 0.22%, CaO: 7.96%, MgO: 80%, K2O: 0.55%, Na2O: 0.02%.

[0060] The method for preparing ceramic tile blanks includes the following steps:

[0061] Prepare the corresponding raw materials according to the weight composition of the ceramic tile body, mix the corresponding raw materials to obtain a mixture; mix 400g of the mixture + 200g of water + 2.0g of adhesive (sodium polycarboxylate) + 0.4g of sodium tripolyphosphate, and ball mill it with a small ball mill jar to obtain a ball mill slurry;

[0062] The requirements for testing ball mill slurry are: fineness 1.8-2.3% (250 mesh sieve), slurry moisture 32-36%, specific gravity 1.68-1.73, and flow rate 40-90 seconds.

[0063] The slurry is dried and granulated using a microwave oven. The moisture content is 6.5-8.5%, and the particle size distribution is as follows: 20 mesh ≤ 2.0%, 20-40 mesh 51-56%, 40-60 mesh 34-38%, 60-100 mesh ≤ 10%, and 100 mesh sieve ≤ 3%.

[0064] After granulation and aging for 30 minutes, weigh out 40g and press into two round cakes, weigh out 30g and press into small strips. Place the two cakes in a constant temperature oven to dry. Adjust the temperature to 180℃ and dry until the moisture content is no more than 1%. Take out the small strips to test the drying strength. Firing the round cakes in a kiln at 1200℃ for about 65 minutes will result in a marble blank with high drying strength.

[0065] Example 2

[0066] A high-dry-strength ceramic tile body, comprising, by weight, the following raw materials:

[0067] 50 parts sodium feldspar, 25 parts washed clay, 35 parts red sand, 12 parts sewage clay, and 2 parts brick base powder.

[0068] The chemical composition of the washed mud is as follows:

[0069] SiO2: 62.7%, Al2O3: 34.04%, Fe2O3: 1.3%, TiO2: 0.06%, CaO: 0.25%, MgO: 0.15%, K2O: 1.38%, Na2O: 0.12%.

[0070] The chemical composition of brick base powder is as follows:

[0071] SiO2: 15%, Al2O3: 3%, Fe2O3: 0.99%, TiO2: 0.22%, CaO: 7.64%, MgO: 72.1%, K2O: 1%, Na2O: 0.05%.

[0072] The method for preparing ceramic tile blanks includes the following steps:

[0073] Prepare the corresponding raw materials according to the weight composition of the ceramic tile body, mix the corresponding raw materials to obtain a mixture; mix 400g of the mixture + 200g of water + 2.0g of adhesive (sodium polycarboxylate) + 0.4g of sodium tripolyphosphate, and ball mill it with a small ball mill jar to obtain a ball mill slurry;

[0074] The requirements for testing ball mill slurry are: fineness 1.8-2.3% (250 mesh sieve), slurry moisture 32-36%, specific gravity 1.68-1.73, and flow rate 40-90 seconds.

[0075] The slurry is dried and granulated using a microwave oven. The moisture content is 6.5-8.5%, and the particle size distribution is as follows: 20 mesh ≤ 2.0%, 20-40 mesh 51-56%, 40-60 mesh 34-38%, 60-100 mesh ≤ 10%, and 100 mesh sieve ≤ 3%.

[0076] After granulation and aging for 30 minutes, weigh out 40g and press into two round cakes, weigh out 30g and press into small strips. Place the two cakes in a constant temperature oven to dry. Adjust the temperature to 180℃ and dry until the moisture content is no more than 1%. Take out the small strips to test the drying strength. Firing the round cakes in a kiln at 1200℃ for about 65 minutes will result in a marble blank with high drying strength.

[0077] Example 3

[0078] A high-dry-strength ceramic tile body, comprising, by weight, the following raw materials:

[0079] 45 parts potassium feldspar, 22 parts washed clay, 30 parts red sand, 11 parts recycled scrap bricks, and 1.5 parts brick base powder.

[0080] The chemical composition of the washed mud is as follows:

[0081] SiO2: 61.5%, Al2O3: 35.2%, Fe2O3: 1.3%, TiO2: 0.06%, CaO: 0.25%, MgO: 0.15%, K2O: 1.38%, Na2O: 0.12%.

[0082] The chemical composition of brick base powder is as follows:

[0083] SiO2: 15%, Al2O3: 3%, Fe2O3: 2%, TiO2: 0.5%, CaO: 8%, MgO: 70.45%, K2O: 1%, Na2O: 0.05%.

[0084] The method for preparing ceramic tile blanks includes the following steps:

[0085] Prepare the corresponding raw materials according to the weight composition of the ceramic tile body, mix the corresponding raw materials to obtain a mixture; mix 400g of the mixture + 200g of water + 2.0g of adhesive (sodium polycarboxylate) + 0.4g of sodium tripolyphosphate, and ball mill it with a small ball mill jar to obtain a ball mill slurry;

[0086] The requirements for testing ball mill slurry are: fineness 1.8-2.3% (250 mesh sieve), slurry moisture 32-36%, specific gravity 1.68-1.73, and flow rate 40-90 seconds.

[0087] The slurry is dried and granulated using a microwave oven. The moisture content is 6.5-8.5%, and the particle size distribution is as follows: 20 mesh ≤ 2.0%, 20-40 mesh 51-56%, 40-60 mesh 34-38%, 60-100 mesh ≤ 10%, and 100 mesh sieve ≤ 3%.

[0088] After granulation and aging for 30 minutes, weigh out 40g and press into two round cakes, weigh out 30g and press into small strips. Place the two cakes in a constant temperature oven to dry. Adjust the temperature to 180℃ and dry until the moisture content is no more than 1%. Take out the small strips to test the drying strength. Firing the round cakes in a kiln at 1200℃ for about 65 minutes will result in a marble blank with high drying strength.

[0089] Example 4

[0090] A high-dry-strength ceramic tile body, comprising, by weight, the following raw materials:

[0091] 50 parts sodium feldspar, 20 parts water-washed clay, 35 parts red sand, 10 parts polishing residue, and 2 parts brick base powder.

[0092] The chemical composition of the washed mud is as follows:

[0093] SiO2: 59.59%, Al2O3: 37%, Fe2O3: 1.4%, TiO2: 0.06%, CaO: 0.25%, MgO: 0.2%, K2O: 1.38%, Na2O: 0.12%.

[0094] The chemical composition of brick base powder is as follows:

[0095] SiO2: 13%, Al2O3: 2%, Fe2O3: 1%, TiO2: 0.4%, CaO: 3.14%, MgO: 79.67%, K2O: 0.75%, Na2O: 0.04%.

[0096] The method for preparing ceramic tile blanks includes the following steps:

[0097] Prepare the corresponding raw materials according to the weight composition of the ceramic tile body, mix the corresponding raw materials to obtain a mixture; mix 400g of the mixture + 200g of water + 2.0g of adhesive (sodium polycarboxylate) + 0.4g of sodium tripolyphosphate, and ball mill it with a small ball mill jar to obtain a ball mill slurry;

[0098] The requirements for testing ball mill slurry are: fineness 1.8-2.3% (250 mesh sieve), slurry moisture 32-36%, specific gravity 1.68-1.73, and flow rate 40-90 seconds.

[0099] The slurry is dried and granulated using a microwave oven. The moisture content is 6.5-8.5%, and the particle size distribution is as follows: 20 mesh ≤ 2.0%, 20-40 mesh 51-56%, 40-60 mesh 34-38%, 60-100 mesh ≤ 10%, and 100 mesh sieve ≤ 3%.

[0100] After granulation and aging for 30 minutes, weigh out 40g and press into two round cakes, weigh out 30g and press into small strips. Place the two cakes in a constant temperature oven to dry. Adjust the temperature to 180℃ and dry until the moisture content is no more than 1%. Take out the small strips to test the drying strength. Firing the round cakes in a kiln at 1200℃ for about 65 minutes will result in a marble blank with high drying strength.

[0101] Example 5

[0102] A high-dry-strength ceramic tile body, comprising, by weight, the following raw materials:

[0103] 48 parts of albite, 24 parts of washed clay, 33 parts of sodium sand, 12 parts of polishing residue, and 1.8 parts of brick base powder.

[0104] The chemical composition of the washed mud is as follows:

[0105] SiO2: 60.24%, Al2O3: 36.2%, Fe2O3: 1.5%, TiO2: 0.06%, CaO: 0.25%, MgO: 0.25%, K2O: 1.38%, Na2O: 0.12%.

[0106] The chemical composition of brick base powder is as follows:

[0107] SiO2: 10%, Al2O3: 2%, Fe2O3: 1%, TiO2: 0.5%, CaO: 5.76%, MgO: 80%, K2O: 0.7%, Na2O: 0.04%.

[0108] The method for preparing ceramic tile blanks includes the following steps:

[0109] Prepare the corresponding raw materials according to the weight composition of the ceramic tile body, mix the corresponding raw materials to obtain a mixture; mix 400g of the mixture + 200g of water + 2.0g of adhesive (sodium polycarboxylate) + 0.4g of sodium tripolyphosphate, and ball mill it with a small ball mill jar to obtain a ball mill slurry;

[0110] The requirements for testing ball mill slurry are: fineness 1.8-2.3% (250 mesh sieve), slurry moisture 32-36%, specific gravity 1.68-1.73, and flow rate 40-90 seconds.

[0111] The slurry is dried and granulated using a microwave oven. The moisture content is 6.5-8.5%, and the particle size distribution is as follows: 20 mesh ≤ 2.0%, 20-40 mesh 51-56%, 40-60 mesh 34-38%, 60-100 mesh ≤ 10%, and 100 mesh sieve ≤ 3%.

[0112] After granulation and aging for 30 minutes, weigh out 40g and press into two round cakes, weigh out 30g and press into small strips. Place the two cakes in a constant temperature oven to dry. Adjust the temperature to 180℃ and dry until the moisture content is no more than 1%. Take out the small strips to test the drying strength. Firing the round cakes in a kiln at 1200℃ for about 65 minutes will result in a marble blank with high drying strength.

[0113] Comparative Example 1

[0114] A high-dry-strength ceramic tile body, comprising, by weight, the following raw materials:

[0115] 40 parts potassium feldspar, 20 parts water-washed clay, 28.8 parts potassium sand, 10 parts polishing residue, and 5 parts brick base powder.

[0116] The remaining conditions are the same as in Example 1.

[0117] Comparative Example 2

[0118] A high-dry-strength ceramic tile body, comprising, by weight, the following raw materials:

[0119] 40 parts potassium feldspar, 20 parts water-washed clay, 28.8 parts potassium sand, 10 parts polishing residue, and 0.5 parts brick base powder.

[0120] The remaining conditions are the same as in Example 1.

[0121] The ceramic tile blanks prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to the following performance tests. The test results are summarized in Table 1 below:

[0122] Among them, the strength of the dried blank is obtained by measuring the pressure and calculating it using an intelligent digital force controller;

[0123] Shrinkage rate is calculated based on the dimensions before and after firing;

[0124] The water absorption rate is calculated by comparing the weight before and after water absorption.

[0125] Table 1

[0126]

[0127] As shown in Table 1, the ceramic tile bodies of Examples 1-5 have a dry strength of 1.80-2.20 MPa, a shrinkage rate of 7.50-7.70%, and a water absorption rate of 0.015-0.02%.

[0128] In Comparative Example 1, when the amount of brick base powder added was 5 parts, the high proportion of brick base powder resulted in a high drying strength of 2.50 MPa, a shrinkage rate of 8.30%, and a water absorption rate of 0.005%.

[0129] In Comparative Example 2, when the amount of brick base powder added was 0.5 parts, the proportion of brick base powder was low, resulting in a low drying strength of 1.50 MPa, a shrinkage rate of 7.35%, and a water absorption rate of 0.05%.

[0130] The above embodiments are preferred implementations of the present invention. In addition, the present invention can be implemented in other ways. Any obvious substitutions without departing from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A ceramic tile body with high drying strength, characterized in that, It consists of the following raw materials in parts by weight: The composition includes 40-50 parts stone powder, 20-25 parts washed clay, 28.8-35 parts medium-temperature sand, 10-12 parts waste material, and 1.2-2 parts brick base powder; the brick base powder contains 65-80% magnesium oxide by weight; the waste material is one or more of polishing slag, recycled scrap bricks, and sewage clay. The dry strength of the high-dry-strength ceramic tile body is 1.

80. 2.20 MPa, shrinkage rate 7.50 7.70%, water absorption rate 0.015 0.02%; The method for preparing the ceramic tile blank includes the following steps: Prepare the corresponding raw materials according to the weight composition of the ceramic tile body; after the raw materials are fully mixed, they are ball-milled; after ball milling, they are granulated; after granulation, they are aged, dried and fired to obtain the ceramic tile body.

2. The high-dry-strength ceramic tile body according to claim 1, characterized in that, The stone powder is one or both of potassium feldspar and sodium feldspar.

3. The high-dry-strength ceramic tile body according to claim 1, characterized in that, The medium-temperature sand is one or more of potassium sand, sodium sand, and red sand.

4. The method for preparing ceramic tile blanks according to any one of claims 1-3, characterized in that, Includes the following steps: Prepare the corresponding raw materials according to the weight composition of the ceramic tile body; After the raw materials are thoroughly mixed, they are ball-milled; after ball milling, they are granulated; after granulation, they are aged, dried and fired to obtain the ceramic tile body.

5. The method for preparing a ceramic tile blank according to claim 4, characterized in that, The ball milling process involves mixing the mixture, water, and desiccant, and then ball milling them in a small ball mill jar.

6. A marble ceramic tile with high drying strength, characterized in that, This includes the ceramic tile blank as described in any one of claims 1-3 or the ceramic tile blank prepared by the preparation method described in any one of claims 4-5.

Citation Information

Patent Citations

  • Production method of once-fired super-spar ceramic tile and ceramic tile

    CN103467103A

  • High-silica porcelain rustic tile and production method thereof

    CN109942288A

  • High-flatness marble tile

    CN110483013A